The measurement of rail passenger crowding : scale development and psychometric properties - Mohd Mahudin, Nor Diana; Cox, Tom; Griffiths, Amanda (Elsevier, 2012)
Research on rail passenger crowding often tacitly subscribes to a measurement of crowding based on density (i.e. physical conditions involving space limitations) and rarely considers the possible role psychological factors may play in measuring this construct. This paper describes the development of an instrument that captures the dimensionality of rail passenger crowding and its relationship to the experience of stress and feelings of exhaustion. The proposed instrument is a 20-item self-rating questionnaire consisting of three sub-scales designed to assess subjective crowding experiences among rail users (n = 525). Findings from the factor analyses generally support the hypothesised three-factor structure of the measurement model (evaluation of the psychosocial aspects of the crowded situation, evaluation of the ambient environment of the crowded situation, and affective reactions to the crowded situation). All sub-scales demonstrate excellent internal consistency and construct validity as well as good convergent and discriminant validity values. The instrument was further tested using structural equation modelling to examine the impact of crowding on commuters' stress and feelings of exhaustion. With the addition of the "passenger density" variable as an indicator of objective measurement of crowding operating in tandem with the crowding sub-scales, the results reveal that: (1) commuters' evaluations of the psychosocial aspects of the crowded situation and of its ambient environment, alongside their rating of passenger density, significantly predict affective reactions to the crowded situation; (2) these affective reactions, in turn, significantly predict stress and feelings of exhaustion; and (3) evaluations of the psychosocial aspects of the crowded situation and of its ambient environment as well as passenger density do not directly predict stress and feelings of exhaustion. The link between rail passenger crowding and the negative outcomes therefore does not appear as a simple, direct relationship, but is mediated by affective feelings of crowdedness. Overall, these results provide satisfactory psychometric properties for the proposed instrument and support its use as an assessment tool for measuring crowding experience in the rail setting.